Global Review of Dairy Recommendations in Food-Based Dietary Guidelines - Comerford, Kevin B.; Miller, Gregory D.; Boileau, Amy C.; Masiello Schuette, Stephanie N.; Giddens, Janice C.; Brown, Katie A. (Frontiers in Nutrition, 2021)
At present, there are approximately 100 countries with national food-based dietary guidelines. While the intent of these guidelines is to inform national-level dietary recommendations, they also tie into global health and sustainable development initiatives, since diet and nutrition are linked to outcomes for all 17 United Nations Sustainable Development Goals. Therefore, key messaging in food-based dietary guidelines plays an important role in both national and global health efforts. However, this type of national-level dietary guidance is not standardized and varies considerably from country to country, and from food group to food group. The main objective of this review is to provide a novel look at dairy food group messaging within global food-based dietary guidelines. Dairy-based messaging from 94 national food-based dietary guidelines was reviewed and grouped by region. The results showed that most nutrient-based dairy messaging relating to underconsumption was focused on calcium, followed by vitamin D, iodine, potassium, and protein; whereas messaging related to overconsumption was focused on saturated fat, added sugars, and salt. Health-based messaging specific to dairy food intake typically coalesced around three health outcomes: 1) bone, teeth, and muscle, 2) cardiometabolic, and 3) gut and immune. Although a fundamental concept of food-based dietary guidelines is to provide dietary guidance in a manner that is both “food-based,” and in the context of “dietary” patterns, most food-based dietary guidelines still express the health value of dairy foods solely in terms of their nutrient content – and often times only in the context of a single nutrient (e.g., calcium).